MEWUJUDKAN LINGKUNGAN MASYARAKAT YANG RAMAH ANAK MELALUI PERLINDUNGAN TERHADAP ANAK DARI PREDATOR KEJAHATAN SEKSUAL - Tundjung Herning Sitabuana; Dixon Sanjaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The growth and development of the children are guaranteed based on Article 28B paragraph (2) of 1945 Constitution of the Republic Indonesia. However, the reality shows an anomaly with rise of cases of sexual violence against children. In SIMFONI's records, age of 13-17 years is one of most vulnerable ages for victims of sexual violence. The forms of sexual violence carried out are in form of obscenity, sexual harassment, rape, exploitation of children for pornography and/or prostitution, showing pornographic content, physical contact with the genital organs of children, and/or forcing children to touch adult genital organs, even incest. According to KEMENPPA’s data, in 2020 there were 215 cases of incest committed by parents, relatives, or family). Through this activity, it aims to socialize legal protection for children in legislation. The implementation of PKM to the community was carried out through several stages, namely surveys, lectures, and Q&A. The results is: (1) public is aware of regulations related to the protection of children from sexual crime predators (criminal sanctions and other forms of legal protection); (2) the emergence of awareness and responsibility to create a child-friendly environment to protect children from sexual crimes. The conclusion sexual crime develops in various forms and modes, both offline and online so increasing public awareness is one way to jointly fight sexual crime predators in addition to strict regulations. Therefore, various forms of similar socialization activities need to be carried out consistently with a wider coverage area.